Barriers to health equity in the United States of America: can they be overcome? - Allen M. Chen (International Journal for Equity in Health)
Abstract Health equity—defined by the Centers for Disease Control and Prevention as " the state in which everyone has a fair and just opportunity to attain their highest level of health—” represents one of the most critical issues facing modern societies. While seemingly an increasing focus of policymakers in recent years, this concept is hardly a novel one. In 1948, the inaugural Constitution of the newly founded World Health Organization clearly stated that “the enjoyment of the highest attainable standard of health is one of the fundamental rights of every human being without distinction of race, religion, political belief, economic or social condition.” Yet nearly a century later, it is arguable how much progress society has made in achieving health equity, particularly in the United States of America where numerous factors at both the level of the individual and population contribute to significant complexity with respect to healthcare access and delivery. The purpose of this review is to thus outline the barriers to health equity so that thoughtful discourse can be promoted to create a more even playing field for the lives of the disadvantaged and underserved in the future.